The Calypso hydrothermal vent field: The seafloor expression of an active submarine low-sulphidation epithermal system, Bay of Plenty, New Zealand - Hocking, Michael W. A. (2007)
The Taupo Volcanic Zone (TVZ) is an area of extensive volcanism and geothermal activity in the North Island of New Zealand. The Calypso Hydrothermal Vent Field (CHVF) is located in an offshore extension of the TVZ on continental shelf, approximately 10 km southwest of the White Island subaerial volcano, at 180-200 m water depth in the Bay of Plenty, New Zealand. Active, moderate temperature (up to 201°C) hydrothermal venting is contained within the Whakatane Graben, a northeast trending depression that has been partially filled by tephra from regional, subaerial volcanic eruptions. Venting of hydrothermal fluid through the volcaniclastic material has led to a varied and geographically distinct assemblage of alteration mineral phases in 4 vent fields in an area of approximately 50 km2. Carbon dioxide is the primary gas phase measured at active vent sites; sulfur is present as reduced H2S gas. The North Vent Field (NVF) is the original site of hydrothermal venting reported at Calypso. Weakly lithified volcaniclastic material recovered from this site has been altered primarily to montmorillonite, a dioctahedral smectite clay; minor mixed-layer clays were also detected. Native sulfur is spatially associated with the pervasively clay-altered samples, and is observed cementing volcaniclastic particles and filling primary pore spaces. Anhydrite mounds were also observed in the NVF. The principal hydrothermal alteration phase at the Southeast Vent Field (SEVF) and the Southwest Vent Field (SWVF) is amorphous silica which has filled the pore spaces between volcaniclastic particles and has overprinted early barite, minor clay, and native sulfur mineral phases. Cinnabar, stibnite, and amorphous arsenic sulfides form crusts on the outer surfaces of the samples as well as filling fractures, and forming inclusions within pyrite-silica veins. Textural relationships indicate volatile metal As, Sb, and Hg deposition is contemporaneous with silica precipitation. Clay-altered, sulfur-rich samples were also recovered from the ...